ANALISIS PERBANDINGAN PENDAPATAN USAHATANI PADI SAWAH IRIGASI METODE SRI (System Of Rice Intensification) DENGAN KONVENSIONAL DI DESA JAYAMULYA KECAMATAN SEMENDAWAI SUKU III KABUPATEN OGAN KOMERING ULU TIMUR - Florence, Eka Anis; Iskandar, Sutarmo; Afriyatna, Sisvaberti (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2016)
Analysis Comparison Irigation Rice Of Earnings SRI Methode (intensification rice of system) and conventional methode In Jayamulya Semendawai Suku III Ogan Komering Ulu Timur Regency. This Research aim to know how big production cost of method rice field paddy conducting of SRI and to know difference of earnings between farmer of method paddy of SRI with conventional method paddy. This research is executed by in Jayamulya Semendawai Suku III Ogan Komering Ulu Timur in June up to August 2016. Research method the used ismethod of survey. Method withdrawal of example of the used is laminated random method do not be proportional (Disproportionate Stratified Random Sampling). Method data collecting is with observation method and direct interview with farmer of example of using statement list which have been prepared previously and assisted with obtained data of existing institutes of its relation with research. Data-Processing ode and used data analysis that is descriptive and quantitative descriptive method qualitative to reply first problems, and to reply second problem that is using earnings formula, is here in after conducted by examination with Test of Rangking Wilcoxon. Result of research indicate that Production Cost farmer paddy using method of SRI differ reality compared to to use conventional method in Jayamulya Semendawai Suku III Ogan Komering Ulu Timur t and Earnings of farmer of paddy using method of SRI differ reality of farmer of paddy using conventional method of hectare per season plant.